Electromyographic responses during elbow movement at two angles with voluntary contraction: Influences of muscle activity on upper arm Biceps Brachii - Nizam Uddin, Ahamed; Sundaraj, Kenneth, Prof. Dr.; R. Badlishah, Ahmad, Prof. Dr.; Matiur, Rahman; Asraf, Ali; Anamul, Islam (Maxwell Scientific Organization, 2013)
Link to publisher's homepage at http://maxwellsci.com